2021
DOI: 10.1002/ange.202100078
|View full text |Cite
|
Sign up to set email alerts
|

Hole‐Storage Enhanced a‐Si Photocathodes for Efficient Hydrogen Production

Abstract: Ferrihydrite (Fh) has been demonstrated as an effective interfacial layer for photoanodes to achieve outstanding photoelectrochemical (PEC) performance for water oxidation reaction owing to its unique hole‐storage function. However, it is unknown whether such a hole‐storage layer can be used to construct highly efficient photocathodes for hydrogen evolution reaction (HER). In this work, we report Fh interfacial engineering of amorphous silicon photocathode (with nickel as HER cocatalyst) achieving a photocurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Inspired by ferrihydrite, FeOOH was applied to the surface of the photocathode to give it an effect similar to that of the hole-storage of ferrihydrite. Research work around ferrihydrite has shown that ferrihydrite has the function of hole-storage on both photoanode and photocathode surfaces and that electrons can selectively pass through its interface to participate in the HER reaction. The hole-storage of ferrihydrite is closely related to the crystalline water molecules in its molecular composition and the chemical environment of Fe 3+ ions . The FeOOH can be obtained from ferrihydrite by annealing at a certain temperature such that it is possible for FeOOH to have a similar effect to hole-storage.…”
Section: Resultsmentioning
confidence: 99%
“…Inspired by ferrihydrite, FeOOH was applied to the surface of the photocathode to give it an effect similar to that of the hole-storage of ferrihydrite. Research work around ferrihydrite has shown that ferrihydrite has the function of hole-storage on both photoanode and photocathode surfaces and that electrons can selectively pass through its interface to participate in the HER reaction. The hole-storage of ferrihydrite is closely related to the crystalline water molecules in its molecular composition and the chemical environment of Fe 3+ ions . The FeOOH can be obtained from ferrihydrite by annealing at a certain temperature such that it is possible for FeOOH to have a similar effect to hole-storage.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, Zhang et al. demonstrated that such a HSL also can be used to construct highly efficient photocathodes for hydrogen evolution reaction (HER) [57] . The efficient and durable a‐Si/Fh/Ni photocathode was designed for solar hydrogen production in alkaline solution.…”
Section: Strategies For Enhancing the Stability Of Photocathodesmentioning
confidence: 99%